2013
DOI: 10.1111/jvh.12064
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sequential use of telbivudine in hepatitis B e antigen‐positive chronic hepatitis B patients with partial responses to pegylated interferon: a pilot study

Abstract: The aim of this study was to investigate the efficacy of sequential use of telbivudine in hepatitis B e antigen (HBeAg)-positive chronic hepatitis B patients with partial responses to pegylated interferon. Patients with partial responses to 48 weeks of pegylated interferon treatment were divided into two groups. In group A, patients stopped pegylated interferon directly without sequential treatment. In group B, patients received sequential treatment with telbivudine 600 mg/day. HBeAg, HBeAb, hepatitis B virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…IFN is an antiviral drug commonly used to treat HBV, due to its dual effects of immunoregulation and viral suppression[23]. The dosage and treatment duration also have important effects on the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…IFN is an antiviral drug commonly used to treat HBV, due to its dual effects of immunoregulation and viral suppression[23]. The dosage and treatment duration also have important effects on the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Fried MW et alshowed that in a study of 265 patients with HBeAg‐positive CHB treated with Peg‐IFNα‐2a for 48 weeks before suspension for 24 weeks, only 16% of patients in the group with HBV DNA levels greater than 5.0 lg copies/mL achieved HBeAg seroconversion. Studies also suggested that switching from Peg‐IFNα‐2a to telbivudine was not only well tolerated and safe but also had a higher HBeAg seroconversion rate compared with both telbivudine monotherapy and Peg‐IFNα‐2a monotherapy …”
Section: Discussionmentioning
confidence: 99%
“…In addition to direct antihepatitis B virus treatment, the immunological effects of telbivudine sequential use after Peg‐IFN have been evaluated and appear to promote HBeAg seroconversion during treatment of CHB, which however requires further study to clarify the mechanism of action and key targets. This is consistent with the results of a study by Huang et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations